Um ohar sobre o olho que olha: adorno do ethos, autoridade do pathos e mudanças discursivas na constituição do feminino na Revista Claudia - Oliveira, Cláudia Neli Borragini Abuchaim de (2014)
Women's magazines, in contemporary times are, as so many other written papers, source of information for the study of the evolution and transformation of the uses of language and, consequently, social, moral, and rhetorical changes. It s through introjection in the dominant discourse that rhetorical tricks, while reflecting the world changes, empower the instituting discourse and settle, by moving the passions, new ways of saying and understanding the constitution of existing values. It is quite clear that women's magazines seek to mirror behaviors and modify them, drawing on the rhetoric of the passions to the discursive construction of the "happy and fulfilled" woman. Thus, the goal of this research is to analyze the rhetorical constitution of the feminine in Claudia magazine, in order to check whether the journal, through time, has renewed its values to accompany his audience. This study is based on a qualitative approach, focused on a main corpus of six editorials of Claudia magazine: October 1961, November 1971, August 1981, October 1991, 2001 and 2011. This study sought to investigate how the rhetoric discourse of Claudia magazine, in fifty years, established, using persuasive tricks, the adornment of the feminine ethos and consolidated happiness and modernity pathos. This study sought to ask also what were the main devices used to fulfill the three basic principles of rhetoric: movere, delectare and docere. Studies of Aristotle (2000) and Perelman and Olbrechts-Tyteca (2000), which guided the research of Reboul (2004), Meyer (2007) and Ferreira (2010), are the analytical basis of this research. The analysis is also based upon certain assumptions of Critical Discourse Analysis of Fairclough (2008). To create the rhetorical context, we draw a historical overview of society and women in Brazil. To prove the persuasive means, we analyze, through the facilities allowed by rhetorical analysis, the effectiveness of the discourse of Claudia magazine. At the end of the investigation, we conclude that, in Claudia, as imagined in the case of this study, the historical subservience of women is abandoned to discursively construct a scenario of happiness, combining the professional with the personal context (often in that order) through "recipes" of good living. With the authority of the media, old speeches are renewed, new discourses stand to live and condition the way of being in the world by rhetorical potential that drives universal or particular audiences, and provide new existential truth". From what we can see, although the language has been modernized through years of publication, there was no change of discursive practices in the magazine in fifty years, since Claudia magazine, from the very beginning, adorns its own ethos and seduces the reader by presenting itself as a kind of "survival manual for women" in society. Claudia magazine built an ethos that accompanied the social changes of its target audience and since its first edition seduced (movere) the auditorium presenting itself as the best friend of women (delectare) and proposing, through its articles (docere) to make all women s life much easier